The Depression in adults with high-functioning autism spectrum disorder: Prevalence, Risk Factors, and Treatments: a systematic review - Marino, Francesco; Brancati, Rosalia; Luongo, Marta; Cacciapuoti, Luca; Gallo, Marica; Ammendola, Angela; Durante, Simona; Di Donna, Salvatore; Morfini, Flavia (Phenomena Journal - International Journal of Psychopathology, Neuroscience and Psychotherapy, 2023)
Background: This study explores the connection between High-Functioning Autism Spectrum Disorder (ASD) and depression in adults. Adults with ASD have a 4-fold higher risk than the general population of developing depression, due to factors such as deficits in Theory of Mind, social isolation, sleep disturbances, and suicidal ideation. While some cognitive and mindfulness-based therapies may help, diagnostic challenges and medication sensitivity complicate management. The aim of this systematic review is (1) to assess the extent of depressive symptomatology among adults with high-functioning autism and (2) to identify specific risk and protective factors associated with the development of depression in adults with high-functioning autism; (2) Methods: This systematic review, following PRISMA guidelines, analyzed the comorbidity of depression in adults with high-functioning autism; 18 articles were included in the analysis at the end of the review; (3) Discussions: Adults with Autism Spectrum Disorder (ASD) are at high risk for depression. Depression can be influenced by autistic traits, complicating the picture. Some risk factors include executive function difficulties, Theory of Mind and facial recognition problems, social isolation and social difficulties, sleep disturbances, and an increased risk of suicide. Further research is needed to understand protective factors and effective treatments for depression in individuals with ASD.